MENINGKATKAN KINERJA SOSIAL DAN PENGELOLAAN LINGKUNGAN MELALUI GREEN ACCOUNTING - Salma, Mustika Auliya; Bayangkara, I.B. Ketut (Gapenas Publisher, 2024)
This study aims to evaluate social performance and environmental management in an effort to prevent environmental pollution through the implementation of green accounting. Using a qualitative design with a case study approach, this study collected data through interviews and direct observation of the environment. The criteria used in this study were designed to be in line with factory operational activities that support the achievement of Sustainable Development Goals (SDGs) 3 and 6. The focus of this study is on target 3.9, which is to reduce the negative impact of pollution on human health to create a healthy and prosperous life, and target 6.3, which aims to improve water quality through pollution reduction and safe wastewater management. This study found that the implementation of green accounting in the research object still has several areas that need improvement, especially in terms of community education and empowerment as well as more effective wastewater management and processing. It is hoped that these findings can be a constructive evaluation material for the Djombang Baru Sugar Factory in improving the implementation of green accounting in the future. The implications of this study can provide a significant contribution in optimizing the implementation of green accounting and increasing the effectiveness of the company's social and environmental responsibility to become better.